Oropharyngeal Candida Colonization in Patients with Acute Myeloid Leukemia - Shiva Shirazian; Soheila Manifar; Reza Safaei Nodehi; Mohaddeseh Shabani (Tehran University of Medical Sciences, 2020)
Objectives: Oral candidiasis has increased in recent years because of the increasing number of high-risk populations. The prevalence of Candida species is different worldwide because of the difference between population characteristics, sampling protocols, and geographic regions. Therefore, determining the more prevalent Candida species in different geographic regions seems essential. This study aimed to determine the more prevalent Candida species in acute myeloid leukemia (AML) patients in comparison with healthy individuals in Iran in 2016. Materials and Methods: Fifty-one patients with AML and 62 healthy controls participated in this cross-sectional study. Samples were collected using a swab rubbed softly on the dorsal surface of the tongue and the oropharynx. The samples were cultured on CHROMagar Candida for 2 to 4 days. For differentiation between albicans and non-albicans species, positive samples were linearly inoculated on Corn Meal Agar with Tween-80. Candida species were identified using a microscope. Data were analyzed using chi-square and Fisher's exact tests. Results: Candida colonization was more frequent in AML patients (41.2%) in comparison with healthy participants (38.7%). Candida glabrata (C. glabrata; 27.5%) and Candida albicans (C. albicans; 32.3%) were the most common isolated species in the AML patients and the controls, respectively. There was a significant decrease in the frequency of C. albicans (P=0.022) and a significant increase in the frequency of C. glabrata (P=0.002) in the AML patients in comparison with the controls. Conclusion: AML patients are more susceptible to candidiasis. C. glabrata is the dominant Candida species in AML patients.